Changing climate, changing economy (The Cournot Centre for Economic Studies series, 2009)
How did climate change become an economic issue? Why is economic discourse so influential on the public policy of climate change? How can it best contribute to the scientific and public debates? Nine eminent scholars explain in this book both how economics has changed environmental understanding and how the study of climate change has modified the economy